The Changes of T-Wave Amplitude and QT Interval Between the Supine and Orthostatic Electrocardiogram in Children With Dilated Cardiomyopathy - Tan, Cheng; Yi, Xiuying; Chen, Ying; Wang, Shuangshuang; Ji, Qing; Li, Fang; Wang, Yuwen; Zou, Runmei; Wang, Cheng (Frontiers in Pediatrics, 2021)
Objectives: Electrocardiogram (ECG) can be affected by autonomic nerves with body position changes. The study aims to explore the ECG changes of children with dilated cardiomyopathy (DCM) when their posture changes. Materials and methods: Sixty-four children diagnosed with DCM were recruited as research group and 55 healthy children as control group. T-wave amplitude and QT interval in ECG were recorded, and their differences between supine and orthostatic ECG were compared in both groups. Subsequently, the children with DCM were followed up and the differences before and after treatment compared. Results: ① Comparisons in differences: Differences of T-wave amplitude in lead II and III, aVF, and V5 and differences of QT interval in lead II, aVL, aVF, and V5 were lower in the research group than in the control group. ② Logistic regression analysis and diagnostic test evaluation: The differences of T-wave amplitude in lead III and QT interval in lead aVL may have predictive value for DCM diagnosis. When their values were 0.00 mV and 30 ms, respectively, the sensitivity and specificity of the combined index were 37.5 and 83.6%. ③ Follow-up: In the response group, the T-wave amplitude difference in lead aVR increased and the difference of QT interval in lead V6 decreased after treatment. In the non-response group, there was no difference before and after treatment. When the combined index of the differences of T-wave amplitude difference in lead aVR and QT interval difference in lead V6, respectively, were −0.05 mV and 5 ms, the sensitivity and specificity of estimating the prognosis of DCM were 44.4 and 83.3%. Conclusions: The differences of T-wave amplitude and QT interval may have a certain value to estimate DCM diagnosis and prognosis.